Assessment of Genetic Diversity of 62 F4 Population of Rapeseed (Brassica Napus L.) Through Multivariate Analysis - Sultana, S; Mahmud, F; Asaduzzaman, M (SAARC Journal of Agriculture, 2021)
Rapeseed (Brassica napus L.) is the best one in respect of oil production. It is the order of the day to take better steps for production and quality improvement of our local cultivars. Broadening of genetic diversity in spring oilseed Brassica napus L. (AACC, 2n = 38), canola is important for continued improvement of this crop. Sixty-two genotypes in F4 generation of Brassica napus L. were evaluated to assess genetic diversity based on randomized complete block design with three replications at the experimental field of Sher-e-Bangla Agricultural University, Dhaka. Different Multivariate analyses were performed to classify 62 genotypes. On the basis of cluster analysis, all the genotypes were classified in five clusters. The cluster IV comprised the maximum number (19) of genotypes followed by same in cluster II (18). The cluster I and V comprised 10 and 9 genotypes respectively. The lowest number of genotypes was present in cluster II. The highest inter-cluster distance (10.309) was observed between the cluster I and IV and the genotypes of these clusters involved in hybridization may produce a wide spectrum of segregating population. The lowest inter-cluster distance (3.513) was observed between the cluster III and IV. The inter-cluster distances were larger than the intra-cluster distances. Considering cluster distance, inter genotypic distance and other agronomic performance G3, G4, G24, G35 and G51 might be suggested for future breeding program. SAARC J. Agric., 19(1): 15-25 (2021)